Statistical evidence for a helical nascent chain - Cruzeiro, Leonor (2021)
We investigate the hypothesis that protein folding is a kinetic, non-equilibrium process, in which the structure of the nascent chain is crucial. We compare actual amino acid frequencies in loops, alpha-helices and beta-sheets with the frequencies that would arise in the absence of any amino acid bias for those secondary structures. The novel analysis suggests that while specific amino acids exist to drive the formation of loops and sheets, none stand out as drivers for alpha-helices. This favours the idea that the alpha-helix is the initial structure of most proteins before the folding process begins.